Abnormal rheology of oxygenated blood in sickle cell anemia - Chien, Shu; Usami, Shunichi; Bertles, John F. (The Journal of Clinical Investigation, 1970)
The viscosity of oxygenated blood from patients with sickle cell anemia (Hb SS disease) was found to be abnormally increased, a property which contrasts with the well recognized viscous aberration produced by deoxygenation of Hb SS blood. Experiments designed to explain this finding led to considerations of deformation and aggregation, primary determinants of the rheologic behavior of erythrocytes as they traverse the microcirculation. Deformability of erythrocytes is in turn dependent upon internal viscosity (i.e. the state and concentration of hemoglobin in solution) and membrane flexibility. Definition of the contribution made by each of these properties to the abnormal viscosity of oxygenated Hb SS blood was made possible by analysis of viscosity measurements, made over a wide range of shear rates and cell concentrations, on Hb SS erythrocytes and normal erythrocytes suspended in Ringer's solution (where aggregation does not occur) and in plasma. Similar measurements were made on the two cell types separated by ultracentrifugation of Hb SS erythrocytes: high density erythrocytes composed of 50 to 70% irreversibly “sickled” cells (ISC) and low density erythrocytes composed of over 95% non-ISC. Under all experimental conditions (hematocrit, shear rate, and suspending medium) the viscosity of ISC exceeds that of normal erythrocytes. The viscosity of non-ISC is elevated only in the absence of aggregation and over intermediate ranges of hematocrit. Analyses of the data reveal (a) an elevated internal viscosity of ISC: (b) a reduced membrane flexibility of both ISC and non-ISC, particularly at low shear rates; and (c) a reduced tendency for aggregation displayed by both cell types. The abnormal viscosity of oxygenated Hb SS blood can be attributed to the altered rheology of ISC and, to a lesser extent, of non-ISC. These studies assign a role to the abnormal rheology of Hb SS erythrocytes in the pathogenesis of sickle cell anemia, even under conditions of complete oxygenation. Images